Analisis Implementasi Pembelajaran Deep Learning pada Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Pung Amanda Nabel; Parlin Wahyuni (Jurnal Dharma PGSD, 2025)
Education plays a crucial role in shaping high-quality human resources capable of competing in the global era. It focuses not only on imparting knowledge but also on instilling moral values, character building, and developing critical thinking skills. However, in practice, many elementary school students still struggle with critical thinking—such as identifying problems, providing logical reasoning, drawing conclusions, and actively participating in discussions and problem-solving. One approach to addressing these issues is "deep learning." This approach emphasizes a deeper understanding by connecting subject matter to real-life situations and encouraging students to think reflectively and analytically. This study aims to describe the implementation of deep learning in Natural and Social Sciences (IPAS) instruction for fifth-grade students at SD Negeri Gedongkuning. A qualitative descriptive method was employed, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that implementing deep learning fosters greater student engagement and enhances critical thinking skills. Nevertheless, challenges remain, including limited instructional time, a lack of supporting facilities, and varying levels of teacher readiness to implement the approach. Therefore, support from schools, the government, teachers, and parents is essential to ensure the optimal implementation of deep learning. (Nuraida & Mulyanti, 2026).